2020
DOI: 10.1186/s12961-020-00571-3
|View full text |Cite
|
Sign up to set email alerts
|

From COVID-19 research to vaccine application: why might it take 17 months not 17 years and what are the wider lessons?

Abstract: It is often said that it takes 17 years to move medical research from bench to bedside. In a coronavirus disease (COVID-19) world, such time-lags feel intolerable. In these extraordinary circumstances could years be made into months? If so, could those lessons be used to accelerate medical research when the crisis eases? To measure time-lags in health and biomedical research as well as to identify ways of reducing them, we developed and published (in 2015) a matrix consisting of overlapping tracks (or stages/p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
80
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(83 citation statements)
references
References 23 publications
0
80
0
Order By: Relevance
“…Despite efforts to develop an effective treatment for COVID-19 and a vaccine against the virus, currently there is nothing yet available that has been shown to be effective. Public o cials in the United States have suggested that a vaccine against Sars-CoV-2 will likely be available in 12 to 18 months [2]; [3].…”
Section: Introductionmentioning
confidence: 99%
“…Despite efforts to develop an effective treatment for COVID-19 and a vaccine against the virus, currently there is nothing yet available that has been shown to be effective. Public o cials in the United States have suggested that a vaccine against Sars-CoV-2 will likely be available in 12 to 18 months [2]; [3].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the simple concept of institutional (private and public) prioritisation of research projects is playing out before our eyes during the COVID-19 pandemic. As Hanney et al describe in follow-up to their previous work, the attention and prioritisation provided at every level for COVID-19 vaccine development will most likely lead to health benefits in a small fraction of the 10 years usually experienced for vaccines [19]. TtP at a local institutional level and COVID-19 at a worldwide level offer strong evidence for greatly improved time to application when priorities are aligned and resources are mobilised.…”
Section: Discussionmentioning
confidence: 95%
“…The importance of partnerships and collaboration in focusing research efforts in an extreme crisis, with a leadership role for the WHO, has been seen in the race to find treatments for COVID-19 and vaccines against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which causes the COVID-19 disease [89]. In many NHRSs across the globe, including in the Philippines, scientists are coming together to participate in WHO's Solidarity Trial, which will test the safety and effectiveness of various possible therapies for treating COVID-19 [90].…”
Section: Who Is Providing Leadership?mentioning
confidence: 99%
“…A key issue going forward is how such cooperation can be built on in strengthening NHRSs into the future. For now, it is recommended that a prospective study be conducted to analyse all that is being done in different NHRSs to speed up research during the pandemic, with a view to taking lessons about cooperation, partnerships and other matters into strengthening NHRSs in the future [89].…”
Section: Who Is Providing Leadership?mentioning
confidence: 99%